MANAJEMEN EKSTRAKURIKULER DAN KONTRIBUSINYA TERHADAP KECERDASAN SISWA DI MADRASAH TSANAWIYAH NEGERI (MTSN) KOTA SAWAHLUNTO - Marzuan Marzuan (al-fikrah: Jurnal Manajemen Pendidikan, 2018)
This study aims to determine the extracurricular management and its contribution to the students' intelligence in Madrasah Tsanawiyah Negeri of Sawahlunto. The method used in this research is field research with qualitative descriptive approach. Data collection techniques used are by observation, interview and documentation. The results showed that extracurricular activities contribute to the formation of the characters and intelligence of the students in MTsN Sawahlunto, in which every extracurricular activity gives positive effect to the students. The students are able to show the good characters in everyday social process both at school and community.